Podręcznik z filozofii. Premiera (współ-etnografia wykładu) - Szwabowski, Oskar; Wężniejewska, Paulina (Hybris, 2017)
In this article we use the co-autoethnography method to analyse the didactic screws. At the same time we are trying to loosen them.